Model order reduction approaches for the optimal design of permanent magnets in electro-magnetic machines. Issue 1 (2015) - Alla, A.; Hinze, M.; Lass, O.; Ulbrich, S.
Abstract: In an electromagnetic machine with permanent magnets the excitation field is provided by a permanent magnet instead of a coil. The center of the generator, the rotor, contains the magnet. Our optimization goal consists in finding the minimum volume of the magnet which gives a desired electromotive force. This results in an optimization problem for a parametrized partial differential equation (PDE). We propose a goal-oriented model order reduction approach to provide a reduced order surrogate model for the parametrized PDE which then is utilized in the numerical optimization. Numerical tests will be provided in order to show the effectiveness of the proposed method.